ETHNOMATHEMATICAL STUDENT WORKSHEETS: DESIGN TRADITIONAL GAME ENGKLEK INDONESIA - Nilam Permatasari Munir; Aswar Anas; Rosdiana Rosdiana (SUJANA: Education and Learning Review, 2023)
Indonesia is known for its traditional games, one of the most popular traditional games for children is engklek. Integrating traditional games into mathematics learning such as providing learning activities into student worksheets will be more interesting for students.  This research aims to determine the effectiveness of the traditional game to improve learning outcomes in the affective and cognitive domains of students. This research is an R&D research with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation), with the subject of 12 junior high school seventh grade students. The data collection techniques used were observation, questionnaire, and test. Data analysis using descriptive statistics averaged and paired sample t-test for hypothesis testing. The result of this research indicates that the final prototype of student worksheets contains two learning activities, that is, the introduction of flat shapes and calculating the area and perimeter of flat shapes.  The worksheet fulfilled the criteria of being very valid and the trial results also fulfilled the criteria of being very practical. The character values obtained from the crank game are cooperation, honesty, fair play, high spirits, and patience, while the cognitive is able to improve math learning outcomes.